Jennifer Mishoe: capstone - Mishoe, Jennifer, artist (Colorado State University. Libraries, 2015)
The artist's statement: Visual art can address two areas of attention that can be deemed separate or integrated - they are the work's appearance and the work's meaning. Many people say you need to understand the meaning of a work of art in order to understand it formally. Others may argue that you can experience it visually without addressing any of its underlying meanings, concepts, or philosophies. During June and July of 2015, I was privileged to travel with colleagues of Colorado State University to QwaQwa and Harrismith, South Africa. There, I experienced the visual arts and arts education of traditional and current South Sotho culture. We were introduced to numerous practicing artists whose work emphasized South Sotho tradition and ritual. Tradition, religion, and spiritual philosophies are concepts that are embedded in the art produced in the region. From this experience, I was personally empowered by how the cultural beliefs and incorporation of art into their daily lives resonated with my own personal and spiritual interests about life and art. Identity is a prominent aspect of traditional South Sotho culture. Their artwork is form of identity, which serves as important element in their culture, heritage and rituals. It functions as a means of communication through the formal appearance of the work, in which one familiar with the culture can recognize the work's origin and meaning. My paintings create a visual language that explores my experience of South Sotho identity, art and culture by addressing its physical properties, symbolism and geometry. An indication of earth and natural material versus the emphasis of geometry as decorative elements is a distinction that I emphasize in my work. Through paint, and alternative materials, such as glass beads and cow manure, my paintings communicate a physical understanding of my experience and the South Sotho artwork.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting